An institution-wide faculty mentoring program at an academic health center with 6-year prospective outcome data. Issue 6 (7th December 2019) - Bonilha, Heather; Hyer, Madison; Krug, Edward; Mauldin, Mary; Edlund, Barbara; Martin-Harris, Bonnie; Halushka, Perry; McGinty, Jacqueline; Sullivan, Joann; Brady, Kathleen; Ranwala, Dayan; Hermayer, Kathie; et al.
Abstract: Background: There is discontent and turnover among faculty at US academic health centers because of the challenges in balancing clinical, research, teaching, and work–life responsibilities in the current healthcare environment. One potential strategy to improve faculty satisfaction and limit turnover is through faculty mentoring programs. Methods: A Mentor Leadership Council was formed to design and implement an institution-wide faculty mentoring program across all colleges at an academic health center. The authors conducted an experimental study of the impact of the mentoring program using pre-intervention (2011) and 6-year (2017) post-intervention faculty surveys that measured the long-term effectiveness of the program. Results: The percent of faculty who responded to the surveys was 45.9% (656/1428) in 2011 and 40.2% (706/1756) in 2017. For faculty below the rank of full professor, percent of faculty with a mentor (45.3% vs. 67.1%, P < 0.001), familiarity with promotion criteria (81.7% vs. 90.0%, P = 0.001), and satisfaction with department's support of career (75.6% vs. 84.7%, P = 0.002) improved. The percent of full professors serving as mentors also increased from 50.3% in 2011 to 68.0% in 2017 ( P = 0.002). However, the percent of non-retiring faculty considering leaving the institution over the next 2 years increased from 18.8% in 2011 to 24.3% in 2017 ( P = 0.02). Conclusions: Implementation of an institution-wide faculty mentoring program significantly improved metrics of career development and faculty satisfaction but was not associated with a reduction in the percent of faculty considering leaving the institution. This suggests the need for additional efforts to identify and limit factors driving faculty turnover.